A geração de resíduos sólidos urbanos e sua influência na gestão urbano-ambiental municipal de Sorocaba/SP - Germano Neto, José Dario [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
In Brazil, rates of urban solid waste generation increase proportionally more than the annual growing of the population. The government, from its federal authority to the municipal spheres, faces increasing challenges for Urban and Environmental management regarding to solid waste in general and, in particular, municipal solid waste. Financial problems added to public health problems that worsen with the serious environmental impacts generated every year. In August 2010 Brazil the PNRS (National Policy on Solid Waste) was approved and sanctioned in which represented a true watershed in the country as a legal framework extremely ambitious and visionary. This work presents the successes and challenges that the municipality of Sorocaba/SP is facing after more than three years of PNRS sanctioned to conduct an Urban and Environmental management suited to the new legal bases towards the subject of solid waste. The results show a large gap between the content proposed by the law and the technical, financial and temporal reality to practical implementation by the municipal government. New legislation and federal incentives, consortiums among the cities, flexible deadlines and environmental education at all levels are certainly some proposals to catalyze processes that aim to solve and overcome the challenges of solid waste

No Brasil as taxas de geração de resíduo sólido urbano aumentam proporcionalmente mais do que o crescimento populacional a cada ano. O poder público, desde a sua instância federal até as esferas municipais, tem desafios crescentes para a gestão Urbano-Ambiental no que se refere a resíduos sólidos de forma geral e, em especial, os resíduos sólidos urbanos. São problemas financeiros que se somam a problemas de saúde pública que se agravam juntamente com os graves impactos ambientais gerados ano a ano. Em agosto de 2010 foi aprovada e sancionada no Brasil a PNRS (Política Nacional de Resíduos Sólidos) que representou um verdadeiro divisor de águas no país com um marco legal extremamente ambicioso e visionário. O presente trabalho traz os desafios e êxitos que o município de Sorocaba/SP vem enfrentando após de mais de três anos de PNRS sancionada para realizar uma gestão Urbano-Ambiental adequada às novas bases legais frente à temática dos resíduos sólidos. Os resultados apontam para uma grande lacuna entre o que está proposto na lei e a realidade técnica, financeira e temporal de implementação prática pelo poder público municipal. Novas legislações e incentivos federais, consórcios intermunicipais, flexibilização de prazos e educação ambiental em todos os níveis são, certamente, algumas propostas para catalisar os processos que visam solucionar e superar os desafios inerentes aos resíduos sólidos
Keywords: Política Nacional de Resíduos Sólidos (Brasil); Resíduos; Resíduos sólidos; Gestão ambiental; Planejamento urbano - Sorocaba (SP)